The Emergence of the Star Formation Main Sequence with Redshift Unfolded by JWST - P. Rinaldi; R. Navarro-Carrera; K. I. Caputi; E. Iani; G. Östlin; L. Colina; S. Alberts; J. Álvarez-Márquez; M. Annunziatella; L. Boogaard; L. Costantin; J. Hjorth; et al. (The Astrophysical Journal)
We investigate the correlation between stellar mass ( M _⋆ ) and star formation rate (SFR) across the stellar mass range ${log}_{10}(M_{\star }/M_{\odot })≈ 6-11$ . We consider almost 50,000 star-forming galaxies at z ≈ 3–7, leveraging data from COSMOS/SMUVS, JADES/GOODS-S, and MIDIS/XDF. This is the first study spanning such a wide M _⋆ range without relying on gravitational lensing effects. We locate our galaxies on the SFR– M _⋆ plane to assess how the location of galaxies in the star formation main sequence (MS) and starburst (SB) region evolves with M _⋆ and redshift. We find that the two star-forming modes tend to converge at ${log}_{10}(M_{\star }/M_{\odot })\lt 7$ , with all galaxies found in the SB mode. However, deeper observations will be instrumental for reaching lower SFRs and M _⋆ to further validate this scenario. By dissecting our galaxy sample in M _⋆ and redshift, we show that the emergence of the star formation MS is M _⋆ dependent: while in galaxies with ${log}_{10}(M_{\star }/M_{\odot })\gt 9$ the MS is already well in place at z = 5–7, for galaxies with ${log}_{10}(M_{\star }/M_{\odot })≈ 7-8$ it only becomes significant at z < 4. Overall, our results are in line with previous findings that the SB mode dominates among low stellar-mass galaxies. The earlier emergence of the MS for massive galaxies is consistent with galaxy downsizing.